2021
DOI: 10.1038/s41598-021-97394-1
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral gender differences are reinforced during the COVID-19 crisis

Abstract: Behavioral gender differences have been found for a wide range of human activities including the way people communicate, move, provision themselves, or organize leisure activities. Using mobile phone data from 1.2 million devices in Austria (15% of the population) across the first phase of the COVID-19 crisis, we quantify gender-specific patterns of communication intensity, mobility, and circadian rhythms. We show the resilience of behavioral patterns with respect to the shock imposed by a strict nation-wide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 48 publications
0
17
1
2
Order By: Relevance
“… 93 A study using mobile phone data from 1·2 million devices in Austria found gender differences in social behaviour during different phases of the COVID-19 pandemic; for example, women avoided larger shopping malls during lockdown, and after lockdown, men returned to their normal social behaviour faster than women. 94
Figure 2 Sexual dimorphism in severity and mortality of COVID-19 Men experience more severe disease courses and more deaths connected to COVID-19, but women appear to be at increased risk of long COVID. Therefore, we argue that sex should be taken in consideration regarding COVID-19 treatment, follow-up, and establishment of public health measures.
…”
Section: Clinical and Public Health Implications Of Sex-based Differe...mentioning
confidence: 99%
“… 93 A study using mobile phone data from 1·2 million devices in Austria found gender differences in social behaviour during different phases of the COVID-19 pandemic; for example, women avoided larger shopping malls during lockdown, and after lockdown, men returned to their normal social behaviour faster than women. 94
Figure 2 Sexual dimorphism in severity and mortality of COVID-19 Men experience more severe disease courses and more deaths connected to COVID-19, but women appear to be at increased risk of long COVID. Therefore, we argue that sex should be taken in consideration regarding COVID-19 treatment, follow-up, and establishment of public health measures.
…”
Section: Clinical and Public Health Implications Of Sex-based Differe...mentioning
confidence: 99%
“…A study conducted in Austria from 1 February to 29 June 2020 showed that during lockdown women, in comparison to men, significantly reduced their own mobility, avoided shopping centers and recreational places more strongly. Moreover, after the lockdown, men returned to normal more quickly than women (Reisch, Heiler, Hurt, Klimek, Hanbury & Thurner, 2021 ). Subsequent research showed that women were more likely than men to use both positive (keeping good relationships with family; maintaining emotional closeness with others through the use of social media; supporting family members or close others; taking care of oneself through diet, exercise, or reading) and negative (being easily angered by others; believing that one's own actions are ineffective; panic buying) coping strategies (Ramos‐Lira, Rafful, Flores‐Celis et al ., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggested resilience and coping strategies play an important role in affecting DP ( Chong et al, 2021 ; Di Giuseppe et al, 2021 ; Di Trani et al, 2021 ; Li P. et al, 2021 ; Nituica et al, 2021 ; Perry et al, 2021 ). Studies also showed gender differences in coping strategies and resilience ( Gargiulo et al, 2021 ; Reisch et al, 2021 ; Yan et al, 2021 ; Zhang X. et al, 2021 ), and this could partially explain the gender differences regarding the differential associations between work hours and sleep duration and DP ( Di Giuseppe et al, 2021 ). As the etiology and mechanism of burnout remain elusive, these findings would help understand the pathogenesis of physician burnout.…”
Section: Discussionmentioning
confidence: 99%